1967
DOI: 10.1029/jz072i007p01863
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of ionospheric currents off the coast of Peru

Abstract: Four Nike‐Apache sounding rockets were launched off the coast of Peru, two near the magnetic dip equator and two to the north of the dip equator. Measurements were made of the magnetic field (for current density determination) with a proton magnetometer and of electron number density (proportional to conductivity) with a DC Langmuir probe. One of the dip equator flights (UNH 65‐4) was launched at the time of maximum negative effect of the lunar current system. The shape of the electrojet current profile is sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 14 publications
3
47
0
Order By: Relevance
“…Later, he estimated the conductivity of the atmosphere that is required to explain Sq variations and attributed this conductivity to the ionization of the atmosphere caused by the solar radiation (Schuster 1908). The existence of the ionospheric currents was later confirmed experimentally by sounding rockets (e.g., Singer et al 1951;Cahill 1959;Davis et al 1967;Maynard 1967;Yabuzaki and Ogawa 1974;Pfaff et al 1997). It is now well established that electric currents of the order of several μA/m 2 flow on the dayside of the E-region ionosphere, in the altitude range of 90-150 km.…”
Section: Observational Overviewmentioning
confidence: 95%
“…Later, he estimated the conductivity of the atmosphere that is required to explain Sq variations and attributed this conductivity to the ionization of the atmosphere caused by the solar radiation (Schuster 1908). The existence of the ionospheric currents was later confirmed experimentally by sounding rockets (e.g., Singer et al 1951;Cahill 1959;Davis et al 1967;Maynard 1967;Yabuzaki and Ogawa 1974;Pfaff et al 1997). It is now well established that electric currents of the order of several μA/m 2 flow on the dayside of the E-region ionosphere, in the altitude range of 90-150 km.…”
Section: Observational Overviewmentioning
confidence: 95%
“…Rocket experiments have been used to provide estimates of the current density along vertical pro®les (Maynard and Cahill, 1965;Maynard, 1967;Sampath and Sastry, 1979), which happened to be very similar. For example, Sampath and Sastry (1979) observed a maximum of the current density at the altitude of 106 km with a vertical half width of 12 km.…”
Section: Rocket Measurementsmentioning
confidence: 99%
“…This fact leads to the further complication of separating the field into its planetary and its incremental parts before being able to interpret properly, not only the external but also the internal contributions (e.g., FORBUSH and CASAVERDE, 1961;ONwUMECHILLI, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…DUHAU and ROMANELLI (1979) analyzed data from the Peruvian dip equator and found that: a) the usual hypothesis that the horizontal component of the planetary internal field is a fraction of 0.4 of the planetary external part (e.g., ONWUMECHILLI, 1967, andFORBUSH andCASAVERDE, 1961) could be inadequate for the studied zone, where the fraction appears to be as large as 0.7; b) currents flowing at F-region heights seem to contribute appreciably to the planetary field at the ground: c) as FORBUSH andCASAVERDE (1961), DAVIS et al (1967), and SHUMAN (1970) concluded, at these latitudes the equatorial electrojet induces within the earth a current that contributes significantly to the geomagnetic daily variations.…”
Section: Introductionmentioning
confidence: 99%